2005
DOI: 10.1007/s11661-005-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure characterization of Alx CoCrCuFeNi high-entropy alloy system with multiprincipal elements

Abstract: A new approach for the design of alloy systems with multiprincipal elements is presented in this research. The Al x CoCrCuFeNi alloys with different aluminum contents (i.e., x values in molar ratio, x ϭ 0 to 3.0) were synthesized using a well-developed arc-melting and casting method. These alloys possessed simple fcc/bcc structures, and their phase diagram was predicted by microstructure characterization and differential thermal analyses. With little aluminum addition, the alloys were composed of a simple fcc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
451
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,034 publications
(505 citation statements)
references
References 23 publications
41
451
0
13
Order By: Relevance
“…[7][8][9][10][11][12][13] Here we demonstrate this effect with Figure 1, which shows the XRD patterns of a series of binary to septenary alloys. It is seen that the phases Figure 1.…”
Section: High-entropy Effectsupporting
confidence: 62%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] Here we demonstrate this effect with Figure 1, which shows the XRD patterns of a series of binary to septenary alloys. It is seen that the phases Figure 1.…”
Section: High-entropy Effectsupporting
confidence: 62%
“…[21,31,32] Thirdly, in HEAs similar disordered and ordered versions of the same base structure often co-exist. [8,[33][34][35] For example, coexistence of BCC and ordered BCC (B2) phases was frequently reported. [8,21,34] Coexistence of FCC and ordered FCC (L1 2 ) phases was also observed.…”
Section: Simple Solid Solution or Intermetallics? One Fundamental Anmentioning
confidence: 99%
“…The separation of the Ni-Al-rich B2 phase (matrix) and the Cr-Fe-rich A2 phase (seeds) seems to lend support to this hypothesis. Spinodal decompositions forming the compositionally different A2 and B2 phases are frequently seen in HEAs, [23,24] and it is interesting to note that in the AlCoCrCuFeNi HEA, the products of the spinodal decomposition are also Ni-Al-rich B2 phase and CrFe-rich A2 phase. [24] The cubic form of the A2 phase, rather than the modulated plates as in References, [23,24] shall originate from the need to minimize the elastic strain energy.…”
Section: Resultsmentioning
confidence: 97%
“…Spinodal decompositions forming the compositionally different A2 and B2 phases are frequently seen in HEAs, [23,24] and it is interesting to note that in the AlCoCrCuFeNi HEA, the products of the spinodal decomposition are also Ni-Al-rich B2 phase and CrFe-rich A2 phase. [24] The cubic form of the A2 phase, rather than the modulated plates as in References, [23,24] shall originate from the need to minimize the elastic strain energy. [25] The nature of the confinement of the region where the spinodal decomposition occurs, for example to within the region circled by the dash-dotted lines in Figure 2, is unclear but it could be related to the boundary effect, as the spinodal decomposition free region locates nicely along the phase boundary between the primary phase and the eutectics.…”
Section: Resultsmentioning
confidence: 97%
“…At room temperature, sample A exhibits a mixed BCC (110) and FCC (111) and al. [6,14] have shown that HEAs exhibited superior high-temperature mechanical behavior until 800 °C. Above this temperature, mechanical properties are deteriorated, which indicates that the alloys are damaged.…”
Section: Methodsmentioning
confidence: 99%